Interaction Toxicity Study between P-glycoprotein Inhibitor (Captopril) and Inducer (Spironolactone) with Their Substrate (Lovastatin) in Male Rats - Aboktifa, Mohammed A.; Abbas, Duraid A. (The Iraqi Journal of Veterinary Medicine, 2020)
An interaction toxicity study was performed to evaluate and compare the effect of P-glycoprotein (P-gp) inhibitor (captopril) and inducer (spironolactone) on their common substrate (lovastatin) that were done by comparing LD50 of the acute study with their chronic form then with those combined therapeutic doses administered for 90 days. Therefore, isobolographic analysis and chronicity index were used as the parameters for this study. Forty rats were allocated into five groups according to the used treatment into: captopril, spironolactone, lovastatin, captopril + lovastatin and spironolactone + lovastatin using up and down method to determine their acute exposure LD50 while ninety rats were used to perform the chronic stage of the study divided equally into six groups according to daily dosing regimen as following G1- control group administered distilled water orally; G2 administered captopril 0.7 mg/kg BW orally; G3-administered spironolactone 1.4 mg/kg BW orally; G4- administered lovastatin 0.57 mg/kg BW orally; G5-administered spironolactone1.4 mg/kg BW orally and lovastatin 0.57 mg/kg BW, G6- administered captopril 0.7 mg/kg BW and lovastatin 0.57 mg/kg BW orally. The results of isobolographic analysis showed that the sort of interaction between P-gp inhibitor (captopril) and lovastatin alone and as combined administration showed to be antagonistic after acute administration while it was synergistic after chronic administration; for P-gp inducer, spironolactone and lovastatin were additive after acute administration and antagonistic after chronic administration. Chronicity index results showed that both captopril and lovastatin accumulated after administered each alone and showed more accumulation after their combined administration while the chronicity index for P-gp inducer (spironolactone) and lovastatin showed less total concentration in the body burden after their combined administration than alone one. In conclusion, it seems that P-gp inhibitor (captopril) causes accumulation of itself and substrate (lovastatin), while P-gp inducer (spironolactone) causes reduction on the body burden of itself as well as lovastatin possibly due to their effects on the kinetics of the body and this may affect the efficacy and safety of drugs.